Microfabrication approaches for oral research and clinical dentistry - Paola Tiozzo-Lyon; Paola Tiozzo-Lyon; Matías Andrade; Camila Leiva-Sabadini; Camila Leiva-Sabadini; José Morales; José Morales; Antonia Olivares; Andrea Ravasio; Sebastian Aguayo; Sebastian Aguayo (Frontiers Media S.A., 2023)
Currently, a variety of laboratory tools and strategies have been developed to investigate in vivo processes using in vitro models. Amongst these, microfabrication represents a disruptive technology that is currently enabling next-generation biomedical research through the development of complex laboratory approaches (e.g., microfluidics), engineering of micrometer scale sensors and actuators (micropillars for traction force microscopy), and the creation of environments mimicking cell, tissue, and organ-specific contexts. Although microfabrication has been around for some time, its application in dental and oral research is still incipient. Nevertheless, in recent years multiple lines of research have emerged that use microfabrication-based approaches for the study of oral diseases and conditions with micro- and nano-scale sensitivities. Furthermore, many investigations are aiming to develop clinically relevant microfabrication-based applications for diagnostics, screening, and oral biomaterial manufacturing. Therefore, the objective of this review is to summarize the current application of microfabrication techniques in oral sciences, both in research and clinics, and to discuss possible future applications of these technologies for in vitro studies and practical patient care. Initially, this review provides an overview of the most employed microfabrication methods utilized in biomedicine and dentistry. Subsequently, the use of micro- and nano-fabrication approaches in relevant fields of dental research such as endodontic and periodontal regeneration, biomaterials research, dental implantology, oral pathology, and biofilms was discussed. Finally, the current and future uses of microfabrication technology for clinical dentistry and how these approaches may soon be widely available in clinics for the diagnosis, prevention, and treatment of relevant pathologies are presented.